P054 Sleep parameters and light exposure in a sub-sample of a brazilian family-based cohort, the baependi heart study. (19th November 2019) - Beijamini, Felipe; Ruiz, Francieli S; Taporoski, Tâmara P; Pereira, Alexandre C; Pedrazzoli, Mario; Knutson, Kristen L; Schantz, Malcolm von
Abstract : Introduction: Sleep is influenced by a multitude of factors, including biological, environmental, as well as sociocultural factors. Evaluating sleep in diverse environments is crucial to develop further understanding of its biological role on health. Methods: Here, we report analysis of a subsample of the Baependi Heart Study. Participants (n=217 [82 male]) underwent actigraphy recordings for at least six consecutive days. Activity and light exposure were recorded using 1-minute epochs and visually scored. Means of bedtime, wake up time, time in bed, sleep duration and sleep efficiency were calculated. Comparisons between sexes were performed using Student's t test, and Pearson correlations between sleep, activity and light exposure also were calculated. Results: Comparisons between sexes yielded significant differences for wake up time (t(218)=-2.76; p=0.006) with women waking up later than men (07:30±01:46 vs 06:54±01:05), time in bed (t(218)=-3.01; p=0.003) and sleep duration (t(218)=-2.60; p=0.010), with longer time in bed (07:55±00:50 vs 07:31±01:03) and sleep duration (07:25±00:56 vs 07:02±01:11) for women. Total light exposure during the 16 hours of highest exposure (M16lu) was lower in women than men (t(218)=4.75; p<0.001. Greater amount of activity during the most active 10-hour continuous period was associated with earlier bedtime (r=-0.186; p=0.006) and earlier wake up time (r=-0.185; p=0.006). Greater light exposure (M16lu) was correlated with earlier waking up time (r=-0.206; p=0.002), shorter time in bed (r=-0.185; p=0.006) and shorter sleep duration (r=-0.135; p=0.045). Discussion: Our finding support the hypothesis that light exposure during daytime is an important factor driving different sleep patterns and timing. This is consistent with the differences we observed between men and women.